2018
DOI: 10.3171/2017.8.spine161266
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal radiographic parameters demonstrate weak correlations with pretreatment patient-reported health-related quality of life measures in symptomatic de novo degenerative lumbar scoliosis: a European multicenter analysis

Abstract: OBJECTIVEPrevious studies have demonstrated that among patients with adult spinal deformity (ASD), sagittal plane malalignment is poorly tolerated and correlates with suboptimal patient-reported health-related quality of life (HRQOL). These studies included a broad range of radiographic abnormalities and various types of ASD. However, the clinical and radiographic characteristics of de novo degenerative lumbar scoliosis (DNDLS), a subtype of ASD, may influence previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
2
29
1
1
Order By: Relevance
“…Although no significant difference of HRQOL in PI-LL modifier was validated in previous study, 9 Ha et al 12 reported that a higher ODI was observed in the “Very Positive” PI-LL modifier group than in the “Positive” group. Both the ODI and JOA scores were statistically significant with “Neutral” and “Very Positive” PI-LL modifier groups, and “Positive” and “Very Positive” PI-LL modifier groups.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although no significant difference of HRQOL in PI-LL modifier was validated in previous study, 9 Ha et al 12 reported that a higher ODI was observed in the “Very Positive” PI-LL modifier group than in the “Positive” group. Both the ODI and JOA scores were statistically significant with “Neutral” and “Very Positive” PI-LL modifier groups, and “Positive” and “Very Positive” PI-LL modifier groups.…”
Section: Discussionmentioning
confidence: 78%
“…However, only weak correlations were found between SVA with the ODI ( r = 0.296) and PT; the numeric rating scale (NRS) for back pain was ( r = −0.260) and SRS pain domain was ( r = 0.282). 9 Similarly, very weak correlations between the ODI with T1PA ( r = 0.137) and PI-LL ( r = 0.137) were demonstrated in another study. 12 Although the results of a Japanese study suggested weak correlation between LL with lumbar function ( r = 0.285), and moderate correlation between LL with VAS score for leg pain ( r = 0.328).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, recent studies do not always show a direct correlation between sagittal imbalance and living quality.- 6,7 Faraj et al 6 conducted a multicenter retrospective study including 74 patients with symptomatic de novo degenerative lumbar scoliosis to investigate the influence of sagittal radiographic parameters on preoperative HRQoL. They found a weak correlation between SVA and the Oswestry Disability Index (ODI) scores (r=0.296, P<0.05).…”
Section: Introductionmentioning
confidence: 99%